PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK DUA TINGGAL DUA TAMU DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 6 X KOTO SINGKARAK KABUPATEN SOLOK - Helvikaduri, Helvikaduri; Mukhni, Mukhni; Febriana, Rina (STKIP PGRI Sumbar, 2013)
The background of this research is students mathematical concept comprehension is low. The type of this research is experimental research by design randomized trial on the subject. Population in this study were all of the students in the class VIII SMPN 6 X Koto Singkarak Kabupaten Solok. The technique in taking the sample is randomly, as an experimental class VIII3 and a control class VIII2. The istrument that researcher used in this study is the analysis of learning quiz and essay from for final test. The data obtained in the analysis by using a normality test, homogenity test and t-test. The analysis of the data found that the mean score of quiz for the first meeting is 82.05, second meeting is 84.11, third meeting is 80,84 and forth meeting 89.21. The mean score of the final test was found that 72.02 in experimental class. It was better than the mean score of control class 60.61.t-test in this research by using one way with software MINITAB get P-value equal to 0,017, it means that less than α = 0,05, this the hypothetical in this study received. In conclusion by applying cooperative learning techniques of Two Stay Two stray is accompanied quiz better than the students concept comprehension by using conventional learning students of class VIII SMPN 6 X Koto Singkarak with a 95% confidence level